MOLECULAR DOCKING OF Crocus sativus PHYTOCHEMICALS AGAINST INDUCIBLE NITRIC OXIDE SYNTHASE AND PHOSPHODIESTERASE-9 IN HEART FAILURE PRESERVED EJECTION FRACTION - Yasmine, Syafira; Firmanto, Neissya Nastiti; Sabrina, Annisa Maya; Khaerunnisa, Siti (Universitas Airlangga, Surabaya, Indonesia, 2023)
Highlights1. Heart failure preserved ejection fraction increases the mortality rate every year.2. Definitive therapy for HFpEF is not well identified.3. Crocus sativus phytochemical has anti-inflammatory and cardioprotective effects due to iNOS and PDE-9 inhibition. AbstractBackground: Heart failure preserved ejection fraction (HFpEF) is a complex disease associated with metabolic disease as a risk factor. A previous study found an association between iNOS and PDE-9 with inflammation and myocardial fibrosis in HFpEF. Objective: This study aimed to identify the potential phytochemicals of Crocus sativus (Saffron) that can inhibit protein iNOS and PDE-9 based on a molecular docking study. Material and Method: A total of fifty phytochemicals were obtained from Dr. Duke's Phytochemical Database and IJAH IPB. Those phytochemicals were screened by using the PyRx application and followed with Lipinski's Rule of Five screening by using SWISS Adme. Ten phytochemicals with lowest binding energy for each protein were docked and visually analyzed using Autodock 4.2 and BIOVIA Discovery Studio Visualizer 2016. Results: The best binding energy between protein-phytochemicals were -9.17 kcal/mol and -8.55 kcal/mol for iNOS and -9.17 kcal,/mol and -9.08 kcal/mol for PDE-9. Conclusion: Delphinidine and malvidin are the recommended inhibitors against iNOS and PDE-9 and must be investigated in further research.